Jews, Gentiles, and Other Animals : the Talmud After the Humanities. - Wasserman, Mira Beth (Divinations: Rereading Late Ancient Religion., 2017)
In Jews, Gentiles, and Other Animals, Mira Beth Wasserman undertakes a close reading of Avoda Zara, arguably the Babylonian Talmud's most scandalous tractate. According to Wasserman, Avoda Zara is where this Talmud joins the humanities in questioning what it means to be a human.